1981
DOI: 10.1152/ajpgi.1981.240.5.g376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atropine on pancreatic response to HCl and secretin

Abstract: In dogs with gastric and pancreatic fistulas, we studied the effect of atropine on the pancreatic secretory response to secretin and intestinal HCl. Atropine sulfate (20 micrograms.kg-1.h-1 iv) significantly depressed basal bicarbonate and protein output. Atropine depressed bicarbonate responses to low doses (62.5, 125, 250, and 500 ng.kg-1.h-1) of secretin but had no significant effect on responses to high doses (1,000 and 2,000 ng.kg-1.h-1). Secretin, with or without atropine, did not stimulate pancreatic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…The only available infor mation concerning the mutual influence of CCK and the parasympathetic nervous sys tem in the control of gallbladder motility has emerged from studies in vagotomized pa tients in whom it has been shown that gall bladder response to CCK is not diminished by vagotomy [20][21][22], The discrepancy could be explained by the fact that the remaining intrinsic postganglionic nerves of the gall bladder still release sufficient acetylcholine to allow a normal response to CCK, or by the existence of local cholinergic mechanisms, in dependent of the vagus nerve. In this context, it is of interest to point out that a similar sit uation occurs at the level of the pancreas, where atropine inhibits bicarbonate response to secretin [23], but vagotomy does not [24,25]. This inhibitory effect of atropine persists even after cutting the extrinsic nerves of the gland [26], suggesting the existence of an in trinsic cholinergic activity, maintained by the intrapancreatic ganglia.…”
Section: Discussionmentioning
confidence: 92%
“…The only available infor mation concerning the mutual influence of CCK and the parasympathetic nervous sys tem in the control of gallbladder motility has emerged from studies in vagotomized pa tients in whom it has been shown that gall bladder response to CCK is not diminished by vagotomy [20][21][22], The discrepancy could be explained by the fact that the remaining intrinsic postganglionic nerves of the gall bladder still release sufficient acetylcholine to allow a normal response to CCK, or by the existence of local cholinergic mechanisms, in dependent of the vagus nerve. In this context, it is of interest to point out that a similar sit uation occurs at the level of the pancreas, where atropine inhibits bicarbonate response to secretin [23], but vagotomy does not [24,25]. This inhibitory effect of atropine persists even after cutting the extrinsic nerves of the gland [26], suggesting the existence of an in trinsic cholinergic activity, maintained by the intrapancreatic ganglia.…”
Section: Discussionmentioning
confidence: 92%
“…5 and Table 1)). Maximal pancreatic secretion in response to secretin is not changed by atropine (Magee, Fragola & White, 1965; Singer, Solomon, Rammert, Caspary, Niebel, Goebell & Grossman, 1981) (Vaysse, Bastie, Pascal, Roux, Martinel, Lacroix & Ribet, 1975). It seems, therefore, that nerves control the sensitivity of the pancreas as a positive modulator of the secretin effect by changing the aparent Km and nH without changing the Vmax.…”
Section: Resultsmentioning
confidence: 99%
“…This has been made possible by the finding that this antagonist does not cross the meningeal barrier and therefore has no central action (Laduron & Lexsen, 1979 Singer et al (1981) have shown that basal cholinergic activity potentiated the effect of secretin on bicarbonate secretion. As atropine reduced the action of dopamine, as well as the action of secretin, it is probable that acetylcholine potentiates the effect of dopamine.…”
Section: Discussionmentioning
confidence: 99%